2014
DOI: 10.1039/c3dt53371a
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Cm(iii) and Am(iii) with human serum transferrin studied by time-resolved laser fluorescence and EXAFS spectroscopy

Abstract: The complexation of Cm(III) with human serum transferrin was investigated in a pH range from 3.5 to 11.0 using time-resolved laser fluorescence spectroscopy (TRLFS). At pH ≥ 7.4 Cm(III) is incorporated at the Fe(III) binding site of transferrin whereas at lower pH a partially bound Cm(III) transferrin species is formed. At physiological temperature (310 K) at pH 7.4, about 70% of the partially bound and 30% of the incorporated Cm(III) transferrin species are present in solution. The Cm(III) results obtained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 76 publications
3
52
0
Order By: Relevance
“…The emission band of the Cm(III) HSA species is shifted about 10 nm relative to the aquo ion. As shown in a recent study for Cm(III) transferrin (λ max = 619.9 nm) the internalization of Cm(III) into the protein structure upon complexation at the transferrin binding sites results in a significantly higher bathochromic shift [47]. Therefore, an internalization of Cm(III) into the HSA protein structure can be excluded.…”
Section: Complexation Studies Of Cm(iii) With Hsa At Varying Phmentioning
confidence: 86%
See 1 more Smart Citation
“…The emission band of the Cm(III) HSA species is shifted about 10 nm relative to the aquo ion. As shown in a recent study for Cm(III) transferrin (λ max = 619.9 nm) the internalization of Cm(III) into the protein structure upon complexation at the transferrin binding sites results in a significantly higher bathochromic shift [47]. Therefore, an internalization of Cm(III) into the HSA protein structure can be excluded.…”
Section: Complexation Studies Of Cm(iii) With Hsa At Varying Phmentioning
confidence: 86%
“…These are mainly amino acids from the protein and potentially additional anions like OH − , CO 3 2etc. The fluorescence lifetime of the Cm(III) HSA species is significantly shorter compared to that of the Cm(III) transferrin species with complexation of Cm(III) at the C-terminal binding site of transferrin (τ = 220 μs) [47]. Complexation of Cm(III) at the transferrin binding site leads to an "internalization" of Cm(III) into the protein structure.…”
Section: Complexation Studies Of Cm(iii) With Hsa At Varying Phmentioning
confidence: 99%
“…This assumption is based on and supported by literature for trivalent lanthanides and actinides. The Eu(III) and Cm(III) binding to Tf is reported several times in literature (Bauer et al, 2014;Binsheng and Harris, 1999;Deblonde et al, 2013;Durbin, 2006;Luk, 1971;O'Hara and Bersohn, 1982;Sturzbecher-Hoehne et al, 2013). Strong experimental evidence for the binding of trivalent actinides (Cm and Am) to Tf was provided by Cooper and Gowing (1981), who separated the serum Tf and albumin fractions after radionuclide spiking and demonstrated that both metal ions were bound to Tf.…”
Section: Trlfs Study Of the Eu(iii) Speciation In Dmem And Complete Cmentioning
confidence: 91%
“…The main function of transferrin, which has two specific Fe 3+ binding sites, is to transport iron. Transferrin in human serum is only 30% ion-saturated, and the vacant sites can bind other metal ions [3,4] and some drug molecules, such as flavanone, doxorubicin hydrochloride and vanadocene dichloride [5,6]. High levels of transferrin receptors have been found on the surface of tumor cells [7,8], possibly due to their increased requirement of iron for metabolism, growth, and development [9], which promoted transferrin to deliver metal ions and drugs to the surface of cancer cells.…”
Section: Introductionmentioning
confidence: 99%